UL11 Protein Is a Key Participant of the Duck Plague Virus in Its Life Cycle - Yang, Linjiang; Wang, Mingshu; Cheng, Anchun; Yang, Qiao; Wu, Ying; Huang, Juan; Tian, Bin; Jia, Renyong; Liu, Mafeng; Zhu, Dekang; Chen, Shun; Zhao, Xinxin; et al. (Frontiers in Microbiology, 2022)
Tegument protein UL11 plays a critical role in the life cycle of herpesviruses. The UL11 protein of herpesviruses is important for viral particle entry, release, assembly, and secondary envelopment. Lipid raft is cholesterol-rich functional microdomains in cell membranes, which plays an important role in signal transduction and substance transport. Flotillin and prohibition, which are considered to be specific markers of lipid raft. However, little is known about the function of duck plague virus (DPV) UL11 in the life cycle of the viruses and the relationship between the lipid raft and UL11. In this study, an interference plasmid shRNA126 for UL11 was used. Results showed that UL11 is involved in the replication, cell to cell spread, viral particle assembly, and release processes. Furthermore, UL11 was verified that it could interact with the lipid raft through sucrose density gradient centrifugation and that function correlates with the second glycine of the UL11. When the lipid raft was depleted using the methyl-β-cyclodextrin, the release of the DPV was decreased. Moreover, UL11 can decrease several relative viral genes mRNA levels by qRT-PCR and Western blot test. Altogether, these results highlight an important role for UL11 protein in the viral replication cycle.